Semantic technology : 8th Joint International Conference, JIST 2018, Awaji, Japan, November 26-28, 2018, Proceedings /: 8th Joint International Conference, JIST 2018, Awaji, Japan, November 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available